2020
DOI: 10.1097/01.aog.0000664596.88451.4b
|View full text |Cite
|
Sign up to set email alerts
|

Early Bird or Night Owl? Investigating the Relationship Between Chronotype and Pregnancy Complications [11L]

Abstract: INTRODUCTION: Chronotype or circadian propensity to be a “morning person” or “evening person” has been predictive of adverse health outcomes in the non-pregnant population. Unfortunately, data regarding chronotype and pregnancy complications including diabetes and hypertension remain limited. METHODS: IRB approved prospective cohort of patients with a singleton pregnancy and no history of pre-existing diabetes were recruited at Augusta University Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Evening chronotype, independent of the presence of diabetes or other comorbidities, has been associated with a greater risk of sleep alterations and mood symptoms [13]. In a previous report on non-diabetic pregnancy, evening chronotype was not related to adverse outcomes nor gestational diabetes (33). Conversely, another study retrospectively evaluating 313 pregnant women showed that lower MEQ was associated with preterm delivery and preeclampsia (34).…”
Section: Discussionmentioning
confidence: 99%
“…Evening chronotype, independent of the presence of diabetes or other comorbidities, has been associated with a greater risk of sleep alterations and mood symptoms [13]. In a previous report on non-diabetic pregnancy, evening chronotype was not related to adverse outcomes nor gestational diabetes (33). Conversely, another study retrospectively evaluating 313 pregnant women showed that lower MEQ was associated with preterm delivery and preeclampsia (34).…”
Section: Discussionmentioning
confidence: 99%